The ability of selected plant essential oils to enhance the action of recommended antibiotics against pathogenic wound bacteria. Issue 2 (March 2017) - Sienkiewicz, Monika; Łysakowska, Monika; Kowalczyk, Edward; Szymańska, Grażyna; Kochan, Ewa; Krukowska, Jolanta; Olszewski, Jurek; Zielińska-Bliźniewska, Hanna
Highlights: The effect of oils with antibiotics against wound bacteria was presented. Cinnamon, clove, thyme and lavender oils the greatest activity showed. An additive and synergistic effect were found for basil, clary sage and rosemary oils. Abstract: The aim of this work was to characterize the ability of essential oils to support antibiotics against pathogenic bacteria in wounds. Gram-positive and Gram-negative bacteria obtained from wound infections were identified according to standard microbiological methods. Essential oils were analysed by GC–FID–MS. The susceptibility of bacteria to antibiotics, essential oils and their combination was assessed using the disc-diffusion method. The Minimal Inhibitory Concentration and Minimum Bactericidal Concentration of the essential oils were established by the micro-dilution broth method. Although cinnamon, clove, thyme and lavender essential oils were found to have the greatest antibacterial activity when used alone, the greatest additive and synergistic effects against pathogenic wound bacteria in combination with recommended antibiotics were demonstrated by basil, clary sage and rosemary oils.